2020
DOI: 10.1103/physrevc.101.044905
|View full text |Cite
|
Sign up to set email alerts
|

Parton-hadron-quantum-molecular dynamics: A novel microscopic n -body transport approach for heavy-ion collisions, dynamical cluster formation, and hypernuclei production

Abstract: We present the novel microscopic n-body dynamical transport approach PHQMD (Parton-Hadron-Quantum-Molecular-Dynamics) for the description of particle production and cluster formation in heavy-ion reactions at relativistic energies. The PHQMD extends the established PHSD (Parton-Hadron-String-Dynamics) transport approach by replacing the mean-field by density dependent two body interactions in a similar way as in the Quantum Molecular Dynamics (QMD) models. This allows for the calculation of the time evolution … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 155 publications
1
73
0
Order By: Relevance
“…3). The missing yields in the tails of the rapidity distributions are estimated by using the d N/dy shape obtained from five transport models (IQMD, PHSD, GiBUU, SMASH) [15][16][17][18]20] (see Sect. 4).…”
Section: Experimental Setup and Data Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…3). The missing yields in the tails of the rapidity distributions are estimated by using the d N/dy shape obtained from five transport models (IQMD, PHSD, GiBUU, SMASH) [15][16][17][18]20] (see Sect. 4).…”
Section: Experimental Setup and Data Analysismentioning
confidence: 99%
“…In the following the data will be compared to five stateof-the-art microscopic transport models: "Isospin Quantum Molecular Dynamics" (IQMD vi.c8) [15], "Parton Hadron String Dynamics" (PHSD v4) [16], "Parton-Hadron-Quantum-Molecular Dynamics" (PHQMD v1) [20], "Simulating Many Accelerated Strongly-Interacting Hadrons" (SMASH v1.5.1) [18,19], and "Giessen Boltzmann-Uehling-Uhlenbeck" (GiBUU, release 2019) [17]. 1 We study the differences between model predictions as observed in the rapidity, transverse momentum, and polar angle distributions of charged pions, in the trends of the A 2 parameter as a function of p cm and system size, and in the predicted abundance of resonances as well.…”
Section: Comparison With Transport Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…These sequential collisions happen more frequently at high densities, and, therefore, the yield of multi-strange hyperons reflect the density in the fireball. The sensitivity of multi-strange hyperon production on the density of the reaction volume, and, hence, on the EOS, has been calculated with the novel PHQMD transport mode [31]. Preliminary results indicate, that in Au-Au collisions at FAIR energies the expected yields of Ξ − and Ω − hyperons and even more of Ξ + and Ω + anti-hyperons, are substantially higher for a soft EOS than for a stiff EOS.…”
Section: The High-density Nuclear-matter Equation-of-statementioning
confidence: 98%
“…This sensitivity is expected to increase at beam energies close to or even below the production threshold, as was the case for kaon production at beam energies around 1 A GeV at SIS18. Preliminary results of calculations with the novel Parton-Hadron-Quantum-Molecular Dynamics (PHQMD) transport model indicate that the yields of Ξ − and Ω − hyperons and even more of Ξ + and Ω + anti-hyperons produced in A+A collisions at FAIR energies depend significantly on the EOS [24]. For a soft EOS, higher densities are reached than for a stiff EOS, and, hence, the number of multiple-collisions increases, resulting in a higher yield of multi-strange hyperons.…”
Section: The High-density Nuclear-matter Equation-of-statementioning
confidence: 99%